The Effect of Principal’s Leadership, Teacher’s Work Motivation, and Teacher’s Work Dicipline on Teacher’s Performance in SMP XYZ Tangerang - Susylawati (Jurnal Ketopong Pendidikan, 2023)
SMP XYZ is a private Christian junior high school located in Tangerang. The leadership of the school principal is one of the main factors influencing teacher performance, along with teachers’ work motivation and work discipline. The improvement of teacher performance greatly depends on how the principal leads, supports, and encourages teachers in carrying out their daily responsibilities. Teacher performance plays a crucial role in determining the overall success and quality of the school. Therefore, the purpose of this study is to examine the effect of the principal’s leadership on teacher performance, the effect of teachers’ work motivation on teacher performance, and the effect of teachers’ work discipline on teacher performance at SMP XYZ, Tangerang. This research employs a quantitative approach by distributing questionnaires to twenty two respondents at SMP XYZ. The collected data were analyzed using multiple regression analysis through the SmartPLS application. Based on the results of the data analysis, the study shows three key findings: first, the principal’s leadership has a positive effect on teacher performance; second, teachers’ work motivation positively influences teacher performance; and third, teachers’ work discipline also has a positive and significant impact on teacher performance.